Systematic Study for Impact of Yoga on Stress, Emotional Stability and performance among Archers from India - N D, Sowmya; Rawat, Vikas (Journal of Neonatal Surgery, 2025)
This study investigates the impact of yoga on stress reduction, emotional stability, and performance among Indian archers. Archery, a sport that requires intense concentration, precision, and resilience, often induces stress and emotional fluctuations, potentially impairing performance. This research systematically examines how yoga practices—including mindfulness, meditation, and visual concentration exercises—can enhance archers' mental and emotional well-being, thereby improving performance outcomes. A literature review of relevant studies from 1998 to 2023 highlights the role of yoga in fostering focus, reducing competitive anxiety, and stabilizing emotions. The study follows a structured methodology, employing both primary and secondary data sources, and adhering to rigorous inclusion criteria for sample selection. The findings underscore yoga’s effectiveness in promoting stress resilience and enhancing performance metrics among archers.